Evidence for the Role of Highly Leukotoxic Actinobacillus actinomycetemcomitans in the Pathogenesis of Localized Juvenile and Other Forms of Early‐Onset Periodontitis - Haraszthy, Violet I.; Hariharan, Govind; Tinoco, Eduardo M.B.; Cortelli, Jose R.; Lally, Edward T.; Davis, Elaine; Zambon, Joseph J. (Journal of periodontology (1970), 2000)
Background: Actinobacillus actinomycetemcomitans leukotoxin is thought to be an important virulence factor in the pathogenesis of localized juvenile and other forms of early‐onset periodontitis. Some highly leukotoxic A. actinomycetemcomitans strains produce 10 to 20 times more leukotoxin than other minimally leukotoxic strains. The distribution, clonality, and intrafamilial transmission of highly leukotoxic A. actinomycetemcomitans were examined in order to determine the importance of leukotoxin in the pathogenesis of periodontitis. Methods: The polymerase chain reaction (PCR) was used to differentiate highly leukotoxic from minimally leukotoxic strains in examining 1,023 fresh A. actinomycetemcomitans isolates and strains from our culture collection. These were obtained from 146 subjects including 71 with localized juvenile periodontitis (LJP), 4 with early‐onset periodontitis, 11 with post‐localized juvenile periodontitis, 41 with adult periodontitis, and 19 periodontally normal subjects. The arbitrarily primed polymerase chain reaction (AP‐PCR) analysis of 30 oral isolates from each of 25 subjects was used to determine the intraoral distribution of A. actinomycetemcomitans clones. AP‐PCR was also used to examine the transmission of A. actinomycetemcomitans in 30 members of 6 families. The clonality of 41 highly leukotoxic A. actinomycetemcomitans strains was evaluated by both AP‐PCR and ribotyping. Results: Highly leukotoxic A. actinomycetemcomitans was found only in subjects with localized juvenile and early‐onset periodontitis. Fifty‐five percent of the LJP subjects harbored highly leukotoxic A. actinomycetemcomitans isolates. Seventy‐three percent of the A. actinomycetemcomitans isolates in these subjects were highly leukotoxic. Highly leukotoxic A. actinomycetemcomitans infected younger subjects (mean age 13.95 years, range 5 to 28 years) than minimally leukotoxic (mean age 35.47 years, range 6 to 65 years). Most subjects were infected with only one A. actinomycetemcomitans genotype. However, PCR of whole dental plaques and subsequent analysis of up to 130 individual oral isolates suggested a possible shift in A. actinomycetemcomitans over time in that a few subjects harbored both highly leukotoxic and minimally leukotoxic strains. AP‐PCR analysis was consistent with intrafamilial A. actinomycetemcomitans transmission. Ribotyping and AP‐PCR analysis confirmed a previous report that highly leukotoxic A. actinomycetemcomitans consists of a single clonal type. Conclusions: This study suggests that localized juvenile and other forms of Actinobacillus‐associated periodontitis are primarily associated with the highly leukotoxic clone of A. actinomycetemcomitans. J Periodontol 2000;71:912‐922.